Preliminary Analysis of Phylogenetic Relationships Among Palaearctic Simuliinae (Diptera, Simuliidae) Inferred from Morphological Characters - Sukhomlin, K.B. (Вестник зоологии, 2012)
Phylogenetic relationships among the Palaearctic genera of the subfamily Simuliinae are analyzed based on the matrix of 100 morphological characters and 37 taxa, including 6 outgroups. Parsimonic analysis was resulted in 3 consensus trees (weighting based on CI, RI and RC indices) of slightly different topology, which show monophyly of the subfamily Simuliinae, tribes Stegopternini, Nevermanniini, Wilhelmiini and Simuliini, and a possible sister-group relationships between the latter two tribes. Tribe Ectemniini is apparently a paraphyletic formation. The analysis also supports transferring of the Stegopternini and Nevermanniini from Prosimuliinae to Simuliinae. Филогенетические отношения между палеарктическими родами Simuliinae проанализированы на основе матрицы из 100 морфологических признаков и 37 таксонов, в том числе 6 внешних групп. В результате парсимонического анализа получены три кладограммы (взвешивание на основе индексов CI, RI и RC) c несколько отличной топологией, показывающие монофилию подсемейства Simuliinae, триб Stegopternini, Nevermanniini, Wilhelmiini и Simuliini и, возможно, сестринские отношения между последними двумя трибами. Триба Ectemniini, — по-видимому, парафилетическое образование. Проведенный анализ также подтверждает правильность перемещения триб Stegopternini и Nevermanniini из Prosimuliinae в Simuliinae.